NON-ENGLISH STUDENTS’ PERCEPTIONS OF THEIR PROBLEMS OVER LEARNING ENGLISH - Nawawi, Aceng; Suparman , Asep; Dewi , Sinta (IPI Garut Press, 2023)
Most of the lecturers has focused on how to make English class more interest without seeing whether there is a problem within. However, this study aims to investigate the non-English students’ perceptions of their problems over learning English in the one of university in Garut, Indonesia. This study adopted the quantitative method with survey design for this research with 75 respondents to find out the research problem. Likert Scale Interpretation was conducted to analyze the data. The result showed that there is a problem over learning English in four skill language: listening’s skill, speaking’s skill, reading’s skill, and also writing skill. In addition to that, the score of each skill was different. Furthermore, speaking’s skill was the skill with the biggest score and need more attention in learning English process.